Search for three-jet resonances in $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2195 authors) (2012)
Results are reported from a search for the production of three-jet resonances in pp collisions at a center-of-mass energy sqrt(s) = 7 TeV. The study uses the data sample collected by the CMS experiment at the LHC in 2011, corresponding to an integrated luminosity of 5.0 inverse femtobarns. Events with high jet multiplicity and a large scalar sum of jet transverse momenta are analyzed for the presence of resonances in the three-jet invariant mass spectrum. No evidence for a narrow resonance is found in the data, and limits are set on the cross section for gluino pair prediction in an R-parity-violating supersymmetry model, for gluino masses greater than 280 GeV. Assuming a branching fraction for gluino decay into three jets of 100%, gluino masses below 460 GeV are excluded at 95% confidence level. These results significantly extend the range of previous limits.